Pengembangan LKPD dengan Pendekatan Saintifik Berbasis Etnomatematika Permainan Tradisional Cak-Belikak pada Materi Geometri Segi Banyak di Kelas IV Sekolah Dasar - Nurochim; Agus Susanta; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
The purpose of this study was to develop worksheets with a scientific approach based on the ethnomathematics of the traditional Cak-Belikak game on polygon geometry material in grade IV elementary schools that are valid and interesting for students. The LKPD development model used is the 4D model from Thiagarajan, which consists of the following stages: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. Development activities are limited to the development stage (Develop). The dissemination stage was not carried out due to the Covid-19 pandemic situation. The results of the analysis of the validity of LKPD using the Aiken's V formula show that the results of the development of LKPD in this study, "Very Feasible" with an average coefficient of validity of the experts' assessment is 0.91. Furthermore, the results of the reliability analysis of the experts' assessments using the Percentage of agreements (R) formula from Cohen Kappa show that the percentage of agreement of the material expert validator is 75% (moderate), the percentage of agreement of the linguist validator is 78% (moderate) and the percentage of agreement of the media expert validator is 84% (strong ). And based on the results of the analysis of students' responses, it shows that the percentage of students' attractiveness to LKPD is 95% (very interesting). Based on the results of this analysis, it shows that the LKPD with a scientific approach based on ethnomathematics of the traditional Cak-Belikak game on polygon geometry material in grade IV of elementary school is feasible and interesting.